Outbreak of gastrointestinal anthrax following eating beef of suspicious origin: Isingiro District, Uganda, 2017. - Miriam Nakanwagi; Alex Riolexus Ario; Leocadia Kwagonza; Freda Loy Aceng; James Mwesigye; Lilian Bulage; Joshua Buule; Juliet Nsimire Sendagala; Robert Downing; Bao-Ping Zhu (Public Library of Science (PLoS), 2020)
INTRODUCTION:Gastrointestinal anthrax is a rare but serious disease. In August 2017, Isingiro District, Uganda reported a cluster of >40 persons with acute-onset gastroenteritis. Symptoms included bloody diarrhoea. We investigated to identify the etiology and exposures, and to inform control measures. METHODS:We defined a suspected case as acute-onset of diarrhoea or vomiting during 15-31 August 2017 in a resident (aged≥2 years) of Kabingo sub-county, Isingiro District; a confirmed case was a suspected case with a clinical sample positive for Bacillus anthracis by culture or PCR. We conducted descriptive epidemiology to generate hypotheses. In a case-control study, we compared exposures between case-patients and neighbourhood-matched controls. We used conditional logistic regression to compute matched odds ratios (MOR) for associations of illness with exposures. RESULTS:We identified 61 cases (58 suspected and 3 confirmed; no deaths). In the case-control study, 82% of 50 case-patients and 12% of 100 controls ate beef purchased exclusively from butchery X during the week before illness onset (MOR = 46, 95%CI = 4.7-446); 8.0% of case-patients and 3.0% of controls ate beef purchased from butchery X and elsewhere (MOR = 19, 95%CI = 1.0-328), compared with 6.0% of case-patients and 30% of controls who did not eat beef. B. anthracis was identified in two vomitus and one stool sample. Butchery X slaughtered a sick cow and sold the beef during case-patients' incubation period. CONCLUSION:This gastrointestinal anthrax outbreak occurred due to eating beef from butchery X. We recommended health education, safe disposal of the carcasses of livestock or game animals, and anthrax vaccination for livestock.